Optical Active Thermal Stable Nanocomposites Using Polybutadiene-Based Polyurethane and Graphene Quantum Dot-MnO2 - Zahra Rahmatpanah; Mir Mohammad Alavi Nikje; Maryam Dargahi (International Journal of Polymer Science)
Synthesis and characterization of new polybutadiene-based polyurethane, graphene quantum dot-MnO2 nanoparticles, and relative nanocomposites were set as the aim of current artwork. For this purpose, a one-pot polymerization approach was employed in preparation of polyurethane through the reaction of amine polyol and toluene diisocyanate (TDI) in presence of DBTDL catalyst. Nanocomposites were synthesized using 1 to 3 incorporation percent of graphene quantum dot-MnO2 nanoparticles in polymer matrix. 1H-NMR and FT-IR spectroscopies confirmed successful synthesis of reaction products including graphene quantum dot-MnO2, polyurethane, and nanocomposites. UV-vis and PL spectrophotometry techniques were applied for achieving optical information of samples. Optical properties of nanocomposites were reserved properly with no great quenching. Thermal stabilities, degradation rates, and thermal characteristics of polyurethane and nanocomposites were investigated using TGA/DTG and DSC analysis. Thermal stability showed direct relationship to nanoparticle content, and 3%wt nanocomposite showed improved thermal behaviour in comparison with pure PU. SEM, XRD, and AFM techniques proved successful nanocomposite synthesis with detecting nanoparticle species and fine nanoparticle dispersion with improved topographic and morphologic characteristics making GQD-MnO2 polyurethane nanocomposites a good candidate for using in optical active and thermal stable coatings.